2020
DOI: 10.3390/cancers12061682
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Analysis of Longitudinal Quantitative MRI Data to Identify Distinct Tumor Habitats in Preclinical Models of Breast Cancer

Abstract: This study identifies physiological tumor habitats from quantitative magnetic resonance imaging (MRI) data and evaluates their alterations in response to therapy. Two models of breast cancer (BT-474 and MDA-MB-231) were imaged longitudinally with diffusion-weighted MRI and dynamic contrast-enhanced MRI to quantify tumor cellularity and vascularity, respectively, during treatment with trastuzumab or albumin-bound paclitaxel. Tumors were stained for anti-CD31, anti-Ki-67, and H&E. Imaging and histology data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 82 publications
3
46
0
Order By: Relevance
“…In previous studies, higher doses of trastuzumab (such as 10 mg/kg) were used to mimic clinical doses and were observed to improve tumor oxygenation [ 18 , 23 , 25 , 26 , 29 ]; however, other studies have reported using up to 35 mg/kg to show sustained response to trastuzumab [ 26 , 30 ]. We previously observed that treating an in vivo model of HER2+ breast cancer with 10 mg/kg trastuzumab prior to doxorubicin significantly improved tumor vascular delivery and sensitized the tumor to chemotherapy [ 23 ], therefore significantly altering sustained tumor burden long after therapy was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, higher doses of trastuzumab (such as 10 mg/kg) were used to mimic clinical doses and were observed to improve tumor oxygenation [ 18 , 23 , 25 , 26 , 29 ]; however, other studies have reported using up to 35 mg/kg to show sustained response to trastuzumab [ 26 , 30 ]. We previously observed that treating an in vivo model of HER2+ breast cancer with 10 mg/kg trastuzumab prior to doxorubicin significantly improved tumor vascular delivery and sensitized the tumor to chemotherapy [ 23 ], therefore significantly altering sustained tumor burden long after therapy was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial variations may change during tumour growth [ 45 ] or with treatment. Imaging-based biomarkers have the potential to evaluate intra-tumoural heterogeneity and its relationship to tumour growth and response to therapy [ 26 , 48 ]. MRI is a useful modality for evaluating spatial and temporal variations in alterations in the biologic characteristics of tumours that may include changes in apoptosis, cellular proliferation, cellular invasion, and angiogenesis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The validity of different DCE-MRI models to assess tumour haemodynamic heterogeneity has not been studied in detail. A recent study identified physiological tumour habitats from DCE-MRI data using parameters derived from Tofts model and evaluated their alterations in response to therapy in preclinical breast cancer models [ 26 ]. Although , , , K ep can be estimated using the commonly used general kinetic or Tofts (GKM) or its extended version (ETM).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, physiological tumor subregions or habitats such as hypoxia and hypermetabolic activity can provide more meaningful biological information, and they do not necessarily follow this simple geometric paradigm 22 , 23 . One caveat is that these physiological tumor subregions are likely cancer type-specific and imaging modality-dependent, and reliable identification of these subregions requires sophisticated algorithms, such as habitat imaging 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%